The Effect of Service Quality and Product Attributes on Customer Loyalty - Abdul Haris (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aims to examine and analyze the effect of service quality and product attributes on customer loyalty (Study on KFC Pengayoman in Makassar). The population in this study are residents in Makassar who are KFC consumers. The sampling method used by the researchers in this study was the proportional Stratified Random Sampling method and a total sample of 70 people was obtained. The type of data used is primary data collected by distributing questionnaires to all respondents. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, validity and reliability tests, classical assumption tests consisting of (normality test, heteroscedasticity test, multicollinearity test) as well as testing all hypotheses through a coefficient of determination test, partial test (test t) and simultaneous test (test f). The results of this study indicate that the service quality variable has no significant effect on customer loyalty at KFC Pengayoman in Makassar. While product attribute variables have a significant effect on customer loyalty at KFC Pengayoman in Makassar. And product attributes are the most dominant variable affecting customer loyalty at KFC Pengayoman Makassar because it has a higher coefficient value and a better significant level than other variables.